Reactions to arthropod allergens, toxins and venoms - Wikel, Stephen (Henry Stewart Talks, 2010)
Host responses to blood feeding arthropods, Skin reactions to bites, stings and contact, Mechanisms of reactions, Molecules responsible for reactions, Characterization of salivary gland gene expression and bioactive molecules in blood feeding arthropod saliva, Blood feeding arthropod modulation of host defenses